PENGARUH PENDAPATAN NELAYAN TERHADAP PENINGKATAN EKONOMI MASYARAKAT DI DESA WERU, KECAMATAN PACIRAN, KABUPATEN LAMONGAN (The Influence of Fishermen’s Income on The Economic Improvement of The Community in Weru Village, Paciran District, Lamongan Regency) - Anam, M. Khairul; Mas'ud, Faisol (Jurnal Ilmiah Sosio Agribis, 2025)
This study analyzes the influence of fishermen's income on improving the economy of coastal communities in Weru Village, Paciran, Lamongan. Quantitative methods were applied through a survey of 86 fishermen through observation, interviews, and questionnaires. Data were analyzed using simple linear regression. The results showed that there was a positive and significant influence of fishermen's income on the community's economy (β = 0.259; p < 0.05). Every 1 unit increase in fishermen's income increased the community's economy by 0.259 units. The coefficient of determination (R²) of 0.675 indicated that 67.5% of the variation in community economic improvement was explained by fishermen's income. The implication is that despite its significant influence, sustainable policies are needed for optimization through: Technology-based empowerment; Diversification of fisheries businesses; Strengthening the marketing of catches. These findings emphasize the crucial role of the fisheries sector in driving the coastal economy.Keywords: fishermen's income, coastal economy, linear regression, Weru Village, community empowerment.